The Impact of Context-Based Capabilities on the Type of Communication of Spaces - Mojgan Khakpour; Guilda Daghighi Masoule; Mehrdad Amirnejad Mojdehi (Civil Engineering Journal, 2018)
Perceiving an architectural work requires a comprehensive understanding of its context, since the context has a direct impact on both the body and the activities. This recognition can be examined from two aspects: the study of natural and geographical conditions and human-based conditions which include the symbolic, religious-cultural, historical, social, and economic values. What has been considered through this article was the effect of these factors on the type of communication between the spaces. Due to the climate and cultural characteristics across Guilan province, it seems that the spaces from their public realm- that is from the neighbourhood spaces to their most exclusive parts- include rooms and closed spaces that have such continuity which was created by the elements of the boundary between these spaces. These elements link the spaces together and lead to a hierarchy of activities. The research question is whether the relationship between spaces and spatial continuity in traditional architecture of Rasht is influenced by the capabilities of the context or not? This is a descriptive-analytical research, which used a qualitative research method. Data collection was carried out by using desk research method   and field observations. The data was analysed through content analysis and independent of numerical documentation within an analogy process. With respect to the effect of filed capabilities on the traditional architecture in Rasht city, first a sample of buildings was selected and the physical elements contributing to continuity of the space have been studied. Then, the effect of the context-based capabilities on them was considered. It was found that these capabilities contributed to formation of the physical elements and behavioural patterns which itself can affect the type of relationship between space and its continuity within old urban tissues of Rasht, including the sensory continuity and the physical continuity between the spaces.